Implantácia gangliových buniek do periférneho nervu - Slováková, D; Mráz, P (Ceskoslovenska neurologie a neurochirurgie, 1991)
The author tried to implant live ganglion cells into a peripheral nerve. They implanted in an experiment 6-8 spinal ganglia of 5-6-day-old rats into the distal part of the n. ischiadicus of an operated full grown rat. Part of the cells of implanted spinal ganglia was unaltered and in their vicinity were numerous groups of non-myelinized axons, probably regenerated processes of these cells. In the perikarya of neurons these were structures of the apparatus of Golgi and granulated endoplasmatic reticula. The mitochondria were in some perikarya large oval, dilated with impaired cristae mitochondriales. These cells were more numerous 42 days after implantation.
Keywords: zvířata; Transplantation, Autologous; Rats; nervus ischiadicus; Sciatic Nerve; Animals; lidé; spinální ganglia; autologní transplantace; Humans; Ganglia, Spinal; krysa rodu Rattus